2012
DOI: 10.1590/s0365-05962012000200005
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma: clinical and pathological aspects in patients seen at the Hospital Universitário Cassiano Antônio Moraes - Vitória - Espírito Santo - Brazil

Abstract: BACKGROUND: Kaposi's sarcoma is a neoplasm of endothelial origin that is divided into four distinct types according to the clinical characteristics and the affected population: Classic (in elder men of Jewish or Mediterranean origin); Epidemic (in patients affected by AIDS); Endemic (in black African men) and Iatrogenic (in patients under immunosuppressive regimens). Human herpesvirus 8 infection is essential but not sufficient for the sarcoma development. OBJECTIVE: To describe the epidemiological, clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 6 publications
1
9
1
5
Order By: Relevance
“…Among all patients, classic KS was the most common (67%), followed by AIDS‐related (31%) and immunosuppressive medication‐related (2%) KS. This contrasts with previous reports from Caucasian and African populations showing AIDS‐associated KS as the most frequently observed form . We also found that the disease was more frequent in males compared with females (10 : 1 ratio), especially in the AIDS‐associated form where all patients were males.…”
Section: Discussionsupporting
confidence: 90%
“…Among all patients, classic KS was the most common (67%), followed by AIDS‐related (31%) and immunosuppressive medication‐related (2%) KS. This contrasts with previous reports from Caucasian and African populations showing AIDS‐associated KS as the most frequently observed form . We also found that the disease was more frequent in males compared with females (10 : 1 ratio), especially in the AIDS‐associated form where all patients were males.…”
Section: Discussionsupporting
confidence: 90%
“…Hiçbir olgunun ailesinde KS tanısı bulunmuyordu. Hastaların özgeçmişine bakıldığında 11'inde (%14, 8) hipertansiyon, dokuzunda (%12,1) diyabet, dördünde hipertiroidi (%5,4), birinde hipotiroid (%1,3), iki (%2,7) hastada psoriasis vulgaris, birinde (%1,3) Behçet hastalığı bulunmaktaydı. Ayrıca iki hastada kolon kanseri, bir hastada ise prostat kanseri vardı.…”
Section: Bulgular Demografik öZelliklerunclassified
“…İyi seyirli, düşük dereceli bir tümör olan KS'de tedavide esas amaçlar semptomları hafifletmek, hastalığın progresyonunu önlemek, hastalığa eşlik eden ödem, uyuşma, psikolojik stresi azaltmaktır. Cerrahi eksizyon, lokal tedaviler ve yaygın olgularda kemoterapi tercih edilebilir 6,8 . Ülkemizin de içinde bulunduğu coğrafyada nispeten sık görülen KKS ile ilgili ülkemizden bildirilen yeterli klinik çalışma bulunmamaktadır.…”
Section: Introductionunclassified
“…1 There are 4 types with principally classified, defined according to histopathological characteristics (new vascular proliferation, erythrocyte extravasation, edema and mononuclear inflammatory cell infiltration): classic, African (endemic), iatrogenic and acquired immunodeficiency syndrome-related. 2 In practice, KS generally presents as one or multiple, asymptomatic, red-purple or brown patches, plaques or nodular skin lesions in the lower extremities. 3 C-Kit is involved in cell signal transduction in many different cell types and it encodes tyrosine kinase receptor (CD117).…”
Section: Introductionmentioning
confidence: 99%